2005
DOI: 10.1002/ird.167
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of field water use efficiency in the Indo-Gangetic Plain of India

Abstract: With a view to enhancing water use efficiency on farmers' fields in the Indo-Gangetic Plain (IGP), a research project was taken up with the involvement of the farmers through the participatory rural appraisal (PRA) technique. Based on PRA and field observations of different cultural practices, gaps between the existing and appropriate water management technologies were established. Suitable interventions were made to fill the gaps and to enhance water use efficiency at field level. The interventions included l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…These results are in general agreement with those of Choudhary et al (2002), Rajput et al (2004), Rajput and Patel (2005) and Jat et al (2006a), who have reported 15-20% water savings in PLL versus TLL. In rice, water savings from PLL compared with TLL were consistently higher in both years in zero-till plots (ZTDSR).…”
Section: Land Levelingsupporting
confidence: 95%
“…These results are in general agreement with those of Choudhary et al (2002), Rajput et al (2004), Rajput and Patel (2005) and Jat et al (2006a), who have reported 15-20% water savings in PLL versus TLL. In rice, water savings from PLL compared with TLL were consistently higher in both years in zero-till plots (ZTDSR).…”
Section: Land Levelingsupporting
confidence: 95%
“…Shifting from high water-guzzling crops such as lowland rice, cotton, and sugarcane to oilseeds, pulses, maize, forages, and agroforestry holds promise to increase water savings in irrigated agriculture. Based on the experience gained from a project conducted in the Indo-Gangetic Plain (IGP), using the participatory rural appraisal techniques, Rajput and Patel (2005) reported that through interventions such as laser levelling, renovation of watercourses, implementing optimal sowing dates for wheat, and demonstrations and training for farmers at least 30% (1.45 MhaÁm) of irrigation water can be saved and an increase in wheat yield by at least 25% can be achieved in farmers' fields.…”
Section: Irrigation Water Management For Improving Water Productivitymentioning
confidence: 99%
“…Sarwar and Perry (2002) use only the term ''water productivity''. Finally, Rajput and Patel (2005) refer to field water use efficiency, but use the term both in respect of saving ''losses'' and increasing productivity -without distinction as to which is WUE and which is irrigation efficiency in the classical sense.…”
Section: Water Use Efficiency (Wue)mentioning
confidence: 99%